Sex differences in the association between visceral adiposity index and biological aging: A cross-sectional analysis of NHANES 1999–2018 with mediation by insulin resistance - Jia Yang; Haifeng Liu; Xupeng Huang; Zimin Fu; Jie Zhou; Tiejun Liu; Weimin Zhao (PLoS ONE, 2025)
Background Aging poses challenges global health and social care systems, with obesity potentially being associated with this process. However, sex differences and the mediating mechanisms underlying this association remain poorly understood. This study investigated sex differences in the associations of visceral adiposity index (VAI) with biological aging (BA) assessed via the Klemera-Doubal method age (KDMAge) and the risk of KDMAge acceleration (KDMAgeAccel), and explored the mediating role of the homeostasis model assessment of insulin resistance (HOMA-IR). Methods According to the National Health and Nutrition Examination Survey (1999–2018), weighted data from 19486 adults were analyzed cross-sectionally. VAI–BA associations were analyzed in the overall population and sex-specific subgroups using multivariable linear and logistic regressions, with nonlinear patterns explored via restricted cubic splines (RCSs) and threshold analyses. Mediation analyses quantified the mediating effects of HOMA-IR. Results VAI correlated positively with BA overall. However, females showed stronger associations than males for each 1-unit VAI increase with KDMAge elevation (βfemale = 1.02, 95% CI: 0.81–1.23; βmale = 0.59, 95% CI: 0.42–0.75) and KDMAgeAccel risk (ORfemale = 1.22, 95% CI: 1.17–1.28; ORmale = 1.10, 95% CI: 1.07–1.13), with all associations remaining significant (P < 0.001). RCSs demonstrated nonlinear positive associations in all cohorts (Pnonlinear < 0.001). Threshold analyses identified that females exhibited a higher VAI threshold for the KDMAge association (3.52 vs. 2.60) despite comparable effect sizes, whereas similar VAI thresholds across sexes were associated with a greater KDMAgeAccel risk in females than in males (75% vs. 36%). HOMA-IR partially mediated VAI–BA associations, with a greater percentage in males than in females in both VAI–KDMAge (21.67% vs. 12.71%) and VAI–KDMAgeAccel risk (27.09% vs. 10.39%) relationships. Conclusion VAI showed a significant positive association with BA, with females demonstrating a stronger association strength and males showing a greater proportion of the association mediated through HOMA-IR.